The Relationship Between Non-Orthographic Language Abilities and Reading Performance in Chronic Aphasia: An Exploration of the Primary Systems Hypothesis. - Madden, Elizabeth Brookshire; Conway, Tim; Henry, Maya L.; Spencer, Kristie A.; Yorkston, Kathryn M.; Kendall, Diane L. (Journal of Speech, Language & Hearing Research, 2018)
Purpose: This study investigated the relationship between non-orthographic language abilities and reading in order to examine assumptions of the primary systems hypothesis and further our understanding of language processing poststroke. Method: Performance on non-orthographic semantic, phonologic, and syntactic tasks, as well as oral reading and reading comprehension tasks, was assessed in 43 individuals with aphasia. Correlation and regression analyses were conducted to determine the relationship between these measures. In addition, analyses of variance examined differences within and between reading groups (within normal limits, phonological, deep, or global alexia). Results: Results showed that non-orthographic language abilities were significantly related to reading abilities. Semantics was most predictive of regular and irregular word reading, whereas phonology was most predictive of pseudohomophone and nonword reading. Written word and paragraph comprehension were primarily supported by semantics, whereas written sentence comprehension was related to semantic, phonologic, and syntactic performance. Finally, severity of alexia was found to reflect severity of semantic and phonologic impairment. Conclusions: Findings support the primary systems view of language by showing that non-orthographic language abilities and reading abilities are closely linked. This preliminary work requires replication and extension; however, current results highlight the importance of routine, integrated assessment and treatment of spoken and written language in aphasia. Supplemental Material: https://doi.org/10.23641/asha. 7403963